Improving Intrapersonal Skills to Overcome the Negative Effects of Overthinking in the Disruption Era - Roy Pieter; Damayanti Nababan; Sandy Ariawan; Siani Listio; Semuel Ruben (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The era of disruption that is being experienced by the entire world population causes negative effects in the form of excessive worry and rumination, which is known as overthinking. Various new habits that must be done as a form of adaptation to the Covid-19 pandemic, including in the field of education, result in adjustments that for some people can be a big problem. Everything, which is good and bad, is spread quickly so that it gives rise to various interpretations for the recipient, which often leads to overthinking. On the other hand, it is believed that the formation of behavior with a certain purpose and purpose cannot grow naturally.  The behavior that is expected for a person must be formed in such a way, because the behavior of the individual is influenced by various things around him. Intrapersonal skills which are one of the soft skills that must be possessed by students are an important part that is expected to be able to counteract the negative effects of overthinking. This study aims to look at the extent of intrapersonal skill influence on overthinking.  The method used in the study was quantitative, with a sample of 100 people. Regression test results showed that intrapersonal skills had a 74.3% effect on overthinking, while 25.7% were influenced by other factors. Thus, the negative effects of overthinking can be prevented by improving intrapersonal skills.